International University Carnival on E-Learning: Embracing AI for Innovative Learning and Inclusive Education - Hafizan, Mohamad Naim (UTeM Melaka, 2025)
The International University Carnival on E-Learning (IUCEL) is a premier annual event that brings together educators, researchers, technologists, and students to celebrate and advance innovation in e-learning. Hosted by Universiti Teknikal Malaysia Melaka (UTeM), IUCEL serves as a dynamic platform for showcasing cutting-edge educational technologies, sharing best practices, and fostering collaboration across institutions and industries. The main objectives of IUCEL are: • To promote excellence and innovation in e-learning practices. • To provide a platform for sharing research, development, and implementation of digital learning tools. • To encourage the development of inclusive and accessible education through technology. • To recognize outstanding contributions in the field of e-learning through various awards and competitions.